The Influence of the Anchored Instruction Model assisted by PHET on Students' Problem Solving Abilities - Dewi, Bq Intan Patmala; Verawati, Ni Nyoman Sri Putu; Hikmawati, Hikmawati; Rahayu, Satutik (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Abstract This research aims to test the effect of the anchored instruction model assisted by PhET on students' physics problem solving abilities in optical instruments at SMAN 1 Sukamulia. The type of research used is quasi experimental with a pretest-posttest control group design. The population is all students in class XI MIPA SMAN 1 Sukamulia, totaling 52 people. The research sample was taken using a saturated sampling technique and class XI MIPA 1 was selected as the experimental class and class XI MIPA 2 was selected as the control class. The experimental class was treated with an anchored instruction model assisted by PhET and the control class was treated with a direct learning model. The research instrument consists of a problem solving ability test (KPM) in the form of a description test of 10 questions taking into account validity, reliability, level of difficulty and differentiability of questions. The KPM pre-test and post-test data were tested for normality and homogeneity, then continued with hypothesis testing using the twin sample t-test. Hypothesis test results obtained that the calculated t value was greater than the t table, so Ha was accepted, so that the PhET-assisted anchored instruction learning model had an effect on ability. Physics problem solving for students at SMAN 1 Sukamulia.